The European emission trading scheme and renewable energy policies: credible targets for incredible results? - Simone Borghesi (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper discusses the merits and limits of the recent European energy policy aimed at reducing carbon emissions, devoting particular attention to the European Trading System of carbon permits and to the measures that the European Union has adopted to promote renewable energy sources. From the comparison of past goals and present results, it is argued that more credible targets for carbon emission reductions and renewable shares would probably help the transition towards an alternative energy system and the necessary reduction of greenhouse gases.
Keywords: L11; Q28; Q38; Q42; Q43; Q48; 330; Pollution; Sustainable Development; Climate Change; Fossil Fuels; Energy Policy; European Union; European Trading System (ETS); Cap-And-Trade; Renewable Energy Sources; Credibility